2019
DOI: 10.1159/000499825
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Behavioural Flexibility of Mantled Howlers (Alouatta palliata) in Response to Anthropogenic Habitat Disturbance

Abstract: While howlers are the most ecologically flexible of the atelines, they must still respond to issues arising from anthropogenic modifications, such as fragmentation or dietary changes. A group of Alouatta palliata living in a highly modified landscape (commensal group) at the Curú Wildlife Refuge in Costa Rica was compared to howlers with limited human influence (control group). The commensal group had a more frugivorous diet than the control group (H = 9.23, p = 0.002) due to crop-foraging of mango fruits. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
(72 reference statements)
0
5
0
2
Order By: Relevance
“…Faced with rapid habitat change, wild chimpanzees in Bulindi adjusted their behavior and ecology to new environmental conditions. Our study, therefore, adds to our expanding knowledge of the behavioral flexibility and ecological resilience of great apes and other primates in response to human disturbances, including deforestation and fragmentation (Hill, 2017; Hockings et al, 2015; Kalbitzer & Chapman, 2018; McKinney, 2019; McLennan, Spagnoletti et al, 2017; Mekonnen et al, 2018; Nowak & Lee, 2013; Spehar et al, 2018). Although this adaptability offers some hope for primate conservation in changing landscapes (McLennan, Spagnoletti et al, 2017), data suggest that human‐caused mortality risk (e.g., from persecution, vehicle collisions, electrocutions, and domestic dogs) impacts primate survival in matrix habitats (Hetman, Kubicka, Sparks, & Tryjanowski, 2019; Katsis et al, 2018; Kibaja, 2014; Lindshield, 2016; Moore et al, 2010; Paterson, 2005; Waters, El Harrad, Chetuan, Bell, & Setchell, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Faced with rapid habitat change, wild chimpanzees in Bulindi adjusted their behavior and ecology to new environmental conditions. Our study, therefore, adds to our expanding knowledge of the behavioral flexibility and ecological resilience of great apes and other primates in response to human disturbances, including deforestation and fragmentation (Hill, 2017; Hockings et al, 2015; Kalbitzer & Chapman, 2018; McKinney, 2019; McLennan, Spagnoletti et al, 2017; Mekonnen et al, 2018; Nowak & Lee, 2013; Spehar et al, 2018). Although this adaptability offers some hope for primate conservation in changing landscapes (McLennan, Spagnoletti et al, 2017), data suggest that human‐caused mortality risk (e.g., from persecution, vehicle collisions, electrocutions, and domestic dogs) impacts primate survival in matrix habitats (Hetman, Kubicka, Sparks, & Tryjanowski, 2019; Katsis et al, 2018; Kibaja, 2014; Lindshield, 2016; Moore et al, 2010; Paterson, 2005; Waters, El Harrad, Chetuan, Bell, & Setchell, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Primates were the order that interacted with the second-highest number of crop genera (43), with corn being the top crop interaction followed by sugarcane and bananas. Primates feeding on crops were often perceived as tolerable by farmers, and they rarely used lethal control measures against them ( Chaves & Bicca-Marques, 2017 ; Lins & Ferreira, 2019 ; McKinney, 2019 ; Rocha & Fortes, 2015 ; Spagnoletti et al, 2017 ). This might be due to them often targeting crops that are not used commercially, which could favor a peaceful coexistence between humans and non-human primate crop-feeders ( Chaves & Bicca-Marques, 2017 ; Rocha & Fortes, 2015 ; Spagnoletti et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The order with the most threatened species was Primates. Thus, it is a good prospect for their conservation that farmers in Latin America tend to tolerate crop-feeding by primates and seldom use lethal control against them ( Chaves & Bicca-Marques, 2017 ; Lins & Ferreira, 2019 ; McKinney, 2019 ). Most of the species that are not considered of least concern are infrequent in the literature, with the most frequent being the Andean bear ( Tremarctos ornatus ) and white-lipped peccary ( Tayassu pecari ), which appeared in four and three studies, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we consider it highly unlikely, though not impossible, that howler monkeys are acting as seed predators for the plant species used for fruitfeeding in our study site. We also identified those tree species present at the study site that have been reported to be used as fruit sources by Alouatta in the Neotropics (Estrada & Coates-Estrada 1984, Wenny 1999, Dias & Rangel-Negrín 2015, Arroyo-Rodríguez et al 2015, McKinney 2019. We think it is probable that those tree species are also being consumed (and their seeds dispersed) by howlers in our study site.…”
Section: Potential Seed-dispersal Servicesmentioning
confidence: 94%